RELATIONS BETWEEN THE BUKHARA EMIRATE AND THE KOKAND KHANATE IN MUHAMMAD HAKIMKHAN TURA’S MUNTAKHAB AL-TAWARIKH - Hotamova Sevara (Modern American Journals, 2025)
This article discusses the significance of Muhammad Hakimkhan Tura’s Muntakhab al-Tawarikh in illuminating the history of the Central Asian khanates up to the second half of the nineteenth century, highlighting the valuable information contained in the work. The purpose of this article is to analyze the main stages of Bukhara–Kokand relations based on the evidence presented in the work and to reveal their socio-political consequences.
Keywords: Geo-economics; trade routes; fortress; northeast; beks; sultans; peace treaty; tribute, Kokand Khanate, Bukhara Emirate, geopolitical objectives, trade relations, Muhammad Ali Khan, Nasrulloh Khan.